A teacher's role in developing early social intelligence at daycare - Lailatul, Azizah; Hilmaliana, Hilmaliana; Nur Mafaiz, Ilma; Khotimah, Husnul; Pertiwi, Eky Prasetya (Journal of Education Technology and Inovation, 2023)
This research is aimed at learning the role of teachers in promoting social intelligence for younger age children. This type of research is a descriptive qualitative. The research is done in kindergarten in the great wrwanman village, the jombang district, jember. Based on the research that has been done that the development of emotional social aspects in preteen age should be considered. The importance of developing emotional social relationships for a child at a young age helps him to understand the environment, the importance of emotional social aspects for a child because he or she is able to socialize. At an early age, children can be taught to build social relationships. Through introduction, children begin to interact and share. Teachers are one of the critical components of the education and teaching learning process. There are three roles of teachers in the process of developing emotional social parenting at rahman's kindergarten. Among other things: a teacher's role as a model in a teacher's learning activity provides a good example for children to appreciate each other, to speak politely (saying please, thank you and sorry). The teacher's role as inspiration in teacher learning is discovering new ideas related to the learning process, inspiring teaching is developing a more creative mind pattern of the child and leaving the child dependent not in class, but becoming a lifelong learning. The teacher's role as a motivator, in developing a child's emotional social through activity